Determination of cadmium in onion (Allium cepa) in Metropolitan Lima - Juan De Dios, Mayra (2022)
A study was carried out to determine cadmium in onion (Allium cepa) in districts of Metropolitan Lima. For the execution of the study, 30 samples were collected of which 10 of them are from North Lima (San Martin de Porres, Los Olivos, Independencia, Comas and Puente Piedra), 10 samples from Lima Center (Cercado de Lima, Jesús María, Pueblo Libre, La Victoria and Rímac) and 10 exhibitions in South Lima (Chorrillos, Villa María del Triunfo, Villa el Salvador, San Juan de Miraflores and Surco). 2 random samples were taken per district and the place of origin of the same was inquired. Cadmium quantification was performed by the atomic absorption method - Graphite Furnace at the Chemical Analysis Services Unit - USAQ (Universidad Nacional Mayor de San Marcos). The minimum and maximum cadmium concentration in onion was 0,02 mg / mg and 0,11 mg / kg, respectively; In addition, the average (0,06 mg / kg) was obtained, exceeding the maximum level established by the WHO / FAO (Codex Alimentarius; Cd = 0,05 mg / kg). Finally, it was determined that the onion samples from Arequipa accumulated a higher concentration of cadmium than those from Lima (Huaral) and La Libertad (Trujillo). The results obtained show that the average concentration of cadmium present in onions exceeds the international standard, which represents a risk for the population. and, therefore, its consumption by the Peruvian population.